2022
DOI: 10.1177/00469580221096277
|View full text |Cite
|
Sign up to set email alerts
|

Child Feeding Practices of Childbearing Mothers and Their Household Food Insecurity in a Coastal Region of Bangladesh

Abstract: The current condition of ensuring WHO-recommended newborn and young child feeding practice is becoming a challenge in many developing nations, particularly in places where family food security is threatened. Because many households in underdeveloped nations frequently face acute food shortage due to poverty, optimal child nutrition is jeopardized. The purpose of this study was to analyze the child feeding behaviors of mothers with children aged 0-24 months and to investigate their household food insecurity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…We found that parental education was both positively and negatively associated with IYCF, depending on the different IYCF components. For example, comparing the reference category with others, parental education, in general, was found to be positively associated with complementary feeding status (5,20,50,53,58,61,67,71,(74)(75)(76)(77), whereas negatively associated with breastfeeding related indicators (6, 21,48,51,52,57,64,65,67,72,73). However, some studies also found positive association between parental education and breastfeeding related indicators (20,49,54,55,60,63,69,70).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that parental education was both positively and negatively associated with IYCF, depending on the different IYCF components. For example, comparing the reference category with others, parental education, in general, was found to be positively associated with complementary feeding status (5,20,50,53,58,61,67,71,(74)(75)(76)(77), whereas negatively associated with breastfeeding related indicators (6, 21,48,51,52,57,64,65,67,72,73). However, some studies also found positive association between parental education and breastfeeding related indicators (20,49,54,55,60,63,69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were conducted at the sub-district level, and one at the district level (Rajshahi district). Among the included studies, the smallest sample size was 400 (20) and the largest sample size was 34,811 (61). The characteristics of the included studies have been summarized in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three dimensions of FI investigated, low food availability & quality, but not poor food access, nor household shocks, was associated with MIDD implementation and maintenance. Negative associations between FI and various infant feeding practices have been reported in Ghana [29], Ethiopia [50][51][52], Bangladesh [32,33,35,53], India [27], and Kenya [36]. Interestingly, in Mongolia, household FI was not associated with MIDD [54].…”
Section: Fi Midd Implementation and Midd Maintenancementioning
confidence: 99%